Dialogicity in Written Specialised Genres, editado por Luz Gil-Salom y Carmen Soler-Monreal - David Sánchez-Jiménez (Universitat Autònoma de Barcelona, 2017)
Reseña de Dialogicity in Written Specialised Genres, editado por Luz Gil-Salom y Carmen Soler-Monreal.